ACTIVITY BASED COSTING METHOD: DETERMINING THE UNIT COST OF HOSPITALS IN SIDOARJO REGENCY - Widiawati, Widiawati; Junjunan, Mochammad Ilyas (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2024)
This study aims to find out how to analyze the activity-based costing method in calculating unit costs at Sidoarjo district hospital. This study emphasizes the concept of activity-based costing in setting rates for hospital inpatient classes based on unit cost calculations. This study uses a descriptive qualitative approach research method. Data obtained by observing and documenting. Test the validity of the data using triangulation and data sources. Then the data analysis technique used in this research is qualitative analysis of interactive models from Miles and Huberman. The results of the study show that in calculating hospitalization rates using the activity-based costing method and traditional methods there are differences in the number of rates set, resulting in differences in several classes, namely Super VVIP B class and class III. Even though some classes get insurance from outside parties, there are still some classes whose rates are cheaper when calculated using traditional methods. This is due to the large number of inpatients who choose class I over other classes, due to differences in facilities. The implication of this study is the difference in the overhead costs for each product or inpatient class, in the traditional method the overhead costs for each inpatient room are only charged to one cost driver. Whereas in the activity-based costing method, overhead costs are charged to each product or inpatient room with several cost drivers.